Interaction of Selected Commercial Antiseptics with Natural Products against Methicillin-Resistant Staphylococcus aureus Strain - Monika Sienkiewicz; Paulina Młodzińska; Anna Kilanowicz; Ewa Dudzińska; Paweł Kwiatkowski (Applied Sciences, 2024)
The carriage of methicillin-resistant S. aureus (MRSA) strains may determine the subsequent occurrence of infection, which mainly affects patients after surgeries. Therefore, its eradication with the use of antibiotics or antiseptics is a crucial method of preventing staphylococcal self-infections. The observed increase in bacterial resistance to known antibacterial substances poses a huge challenge to scientists. The aim of this study was to analyze the interaction of selected commercial antiseptics (Braunol, CITROclorex 2%, Microdacyn 60 Wound Care, Octenisept and Prontoderm Solution) with natural products (carvacrol, β-citronellol, geraniol, eugenol, farnesol, (-)-menthone, eucalyptol, limonene, linalyl acetate and trans-anethole) against the MRSA standard strain. The antistaphylococcal activity of commercial antiseptics in combination with natural products against MRSA was determined using the checkerboard method. The obtained results showed that most combinations decreased the MIC level of the commercial antiseptic and natural compounds. A statistically significant decrease in the MIC value of the antiseptic and natural constituent was observed for the Braunol–β-citronellol combination. Such a significant decrease in the MIC value of the natural compound against the analyzed strain was also detected for the Octenisept–β-citronellol and Prontoderm Solution–β-citronellol combinations. The interaction analysis showed that out of all 20 combinations of individual antiseptics with substances of natural origin, two combinations showed a synergistic effect (Braunol–β-citronellol, Braunol–carvacrol), and three combinations showed an additive effect (Braunol–eugenol, Braunol–geraniol, Prontoderm Solution–β-citronellol). The use of Braunol in combination with β-citronellol or carvacrol may become an alternative method of eradicating MRSA strains. However, further studies are needed to determine the toxicity of the analyzed combinations.